The impact of editorial content on the political agenda in Germany: Theoretical assumptions and open questions regarding a neglected subject in mass communication research - Christiane Eilders (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
This paper takes the perspective of media as autonomous actors in the political process. In editorials media legitimately try to influence the agendas and decisions of the political system not only by explicitly expressing their opinions on issues and political actors, but also by assigning relevance to certain issues or subissues and framing and interpreting political events according to their editorial stance. It may be assumed that the impact of editorials on the political system depends on the degree of issue focusing and opinion consonance: If different newspapers comment on the same issues and express similar opinions, considerable pressure is put on the political system. Our theoretical considerations of the role of “media opinion” in the political process and a review of the relevant agenda-building literature indicate a research gap regarding the impact of editorials on the political agenda. The empirical project outlined in this paper intends to help closing this gap. Editorial content of the leading German newspapers between 1993 and 1998 will be related to data on statements and decisions of the political system in order to investigate under what circumstances media consonance is achieved and how the political system reacts to it. – – Dieser Beitrag betrachtet Medien als autonome Akteure im politischen Prozeß. In Kommentaren nehmen sie ihr Recht in Anspruch, Einfluß auf die Agenden und Entscheidungen des politischen Systems auszuüben, indem sie Probleme und Akteure explizit bewerten, aber auch bestimmten Themen oder Themenaspekten Relevanz zuweisen und politische Ereignisse entsprechend ihrer redaktionellen Linie deuten und interpretieren. Man kann davon ausgehen, daß der Einfluß von Kommentaren auf das politische System vom Ausmaß an Themenfokussierung und Meinungskonsonanz abhängt: Wenn unterschiedliche Zeitungen die gleichen Themen kommentieren und ähnliche Meinungen zum Ausdruck bringen, steigt der Druck auf das politische System. Unsere theoretischen Überlegungen zur Rolle von “Medienmeinung” im politischen Prozeß und ein Überblick über relevante Arbeiten zum Agenda-Building zeigen, daß der Einfluß von Kommentaren auf die politische Agenda bisher nur ungenügend untersucht wurde. Das empirische Projekt, das hier vorgestellt wird, soll zur Schließung dieser Forschungslücke beitragen. Um festzustellen, unter welchen Bedingungen eine übereinstimmende Kommentierung entsteht und wie das politische System darauf reagiert, sollen Kommentarinhalte aus überregionalen Tageszeitungen zwischen 1993 und 1998 mit Daten über Äußerungen und Entscheidungen im politischen System in Beziehung gesetzt werden.
Keywords: 300